(untitled) (American Journal of Interdisciplinary Research and Innovation, 2022)
Issues related to the Resolution of Electoral Disputes in the Albanian legislation began to be addressed only after the change of the government system, in the early 90s. The Constitution of the Republic of Albania, approved on November 28, 1998, created the necessary legislative basis for dealing with these issues in accordance with international legal standards. According to the Albanian legislation the Electoral Administration Zone Commissions and the Central Election Commission are responsibly the administrative review of complaints and appeals. The Electoral College as an ad hoc electoral court-has the responsibility to judge the electoral appeals. The Albanian legal framework related to the Resolution of Electoral Disputes is developed having as their main objective the respect of the standards that condition equality in the right to appeal, transparency and increased effectiveness in the administration and adjudication of complaints and appeals.International observers have evaluated positively the efforts and results achieved in the legislative process for the drafting of the legal framework for the administrative review and trial of electoral complaints and appeals in Albania.The developments in the Albanian electoral legislation for the Resolution of Electoral Disputes are guided by the recommendations given by the international observers of the OSCE/ODIHR and the standards set by the Venice Commission.The changes in the Albanian legislation for the Resolution of Electoral Disputes have as their main objective the respect of the standards that condition equality in the right to appeal, transparency and increased effectiveness in the administration and adjudication of complaints and appeals.